Semantic Study of Salem Batik Motifs in Brebes Regency, Central Java - sari, Yati Putpita; Astuti, Eka Yuli (Universitas Muria Kudus, 2025)
This research analyzes the semantic meaning of Salem batik motifs, an intangible cultural heritage from Brebes Regency, Central Java. Salem batik features distinctive motifs adapted to the local environment and socio-cultural conditions, categorized into color (contemporary) and classic motifs. The primary focus of this study is to examine the lexical meaning, classification of motifs based on their references, and the cultural meaning embedded in these batik motifs. The descriptive qualitative method was employed. The research was conducted in Bentar Village, Salem District, Brebes Regency, at two Salem batik production houses, namely Just 2, which is managed by Mrs. Aan Darwanti, and Mawar Batik, which Mrs. Pupung Kurnaesih manages. Data analysis followed the agih method, involving data reduction, presentation, analysis, and conclusion drawing. The findings identify thirty lexicons of Salem batik motifs classified into three categories. Based on their lexical meaning, the motifs are divided into fourteen color motifs (kangkung, merica, gunung lio, beras tabur, bunga kapas, daun anggur, daun pepaya, kembang kopo, rambutan, wayang, simbar, melati, titik separoh, bawang bebek) and sixteen classic motifs (kopi pecah, manggar, gribig dinding, gribig miring, jaring, sidamukti ukel, ukel pisang, sawat rante, ukel kail, uneg, galaran, puger, parang, sengkawung, galaran kawung, galaran bawang bebek). Based on their references, the motifs are classified into seven categories: flora (kangkung, merica, beras tabur, bunga kapas, daun pepaya, daun anggur, kembang kopo, rambutan, kopi pecah, manggar, puger, simbar, melati), floral stylization (ukel pisang, ukel kail, uneg), geometric (titik separoh, gribig dinding, gribig miring, jaring, sidamukti ukel, galaran, parang, sengkawung, galaran kawung), figurative (wayang), natural/geographical (gunung lio), artefactual (sawat rante), and combinative (bawang bebek, galaran bawang bebek). The overall cultural meaning of these Salem batik motifs reflects the worldview, values, and identity of the Salem community.